Physicochemical Properties and Bioactive Compounds of Three Varieties of Melon (Cucumis melo) Seed Oils - Maryam Jalili; Ladan Rashidi (Journal of Food Quality)
The physicochemical composition of the oil extracted from three different melon seed varieties (named Uzbek-Russian, Soski, and Soski Green), which were collected from three various geographical parts of Iran (north, northeast, and center), was determined in 2021 and 2022. The macronutrient components, fatty acid profile, sterol compounds, phenolic compounds, tocopherols, and oxidative stability of the melon seed oils were determined. The oil content of melon seeds ranged from 43.3% to 47.3%. Linoleic (54.48% to 60.35%), oleic (24.35% to 28.03%), and palmitic acids (10.15% to 12.65%) were the predominant fatty acids. No significant differences were observed between the three cultivars and between the 2 years of the study in terms of macronutrient components and fatty acid profiles (p>0.05). Twelve different phenolic compounds were identified, of which caffeic acid was the major compound, ranging from 39.74% ± 1.70% (Soski Green) to 63.45% ± 1.25% (Uzbek-Russian). The amounts of caffeic acid and oxidative stability of Uzbek-Russian were significantly higher than those in the two other cultivars. β-Sitosterol (approximately 60%) and γ-tocopherol (71.6 to 84.07 mg/100 g) were the major sterol and tocopherol compounds, respectively. The results indicated that the physical and chemical specifications of the three investigated melon seed oils were stable for two consecutive years. Therefore, melon seed oil is a rich source of bioactive compounds and could be introduced as a healthy oil for human consumption.